Integrated multi-biomarker responses in Mozambique tilapia, Oreochromis mossambicus under acute and chronic Diazinon® exposures. Issue 3 (16th March 2023) - Saha, Shubhajit; Chandra Saha, Nimai; Chatterjee, Arnab; Banerjee, Priyajit; Garai, Pramita; Sharma, Pramita; Patnaik, Lipika; Nayak, Susri; Dhara, Kishore; Chukwuka, Azubuike V.; Faggio, Caterina
ABSTRACT : The pesticide ecosystem impacts are very diverse, and depending on their persistence could exert their intrinsic toxicity within an acute to a chronic timeframe. This study examined the toxic effects of Diazinon on haematological and biochemical endpoints in Oreochromis mossambicus after chronic exposure. After a prior range fining test, fishes were exposed to predetermined diazinon concentrations (T1-0.906 mg/L) and (T2-1.812 mg/L) and sampled after 28 days for toxicity endpoints. In Diazinon-exposed fish, haemoglobin content, Total Red Blood Cells, Total White Blood Cells, and MCH levels were substantially lower ( p < 0.05) than in the control fish group. The total blood glucose concentrations in treated fish were substantially greater ( p < 0.05) than in the control group, whereas serum protein concentrations were significantly lower ( p < 0.05). Observation for most biomarkers revealed patterns of decreasing values with increasing toxicant concentration and exposure duration. The integrated indices (IBR and BRI) indexes were used to provide visual and understandable depictions of toxicity effects and emphasised the relativity of biomarkers in terms of sensitivity and magnitude or severity of responses under graded toxicant exposures. In acute and chronic diazinon exposure circumstances, the analysed metrics show significant impairment to Oreochromis mossambicus .